2014
DOI: 10.1016/j.tube.2014.03.007
|View full text |Cite
|
Sign up to set email alerts
|

In vitro–in vivo activity relationship of substituted benzimidazole cell division inhibitors with activity against Mycobacterium tuberculosis

Abstract: Structure based drug design was used to develop a compound library of novel 2,5,6- and 2,5,7-trisubstituted benzimidazoles. Three structural analogs, SB-P1G10, SB-P8B2 and SB-P3G2 were selected from this library based on previous studies for advanced study. In vitro studies revealed that SB-P8B2 and SB-P3G2 had sigmoidal kill-curves while in contrast SB-P1G10 showed a narrow zonal susceptibility. The in vitro studies also demonstrated that exposure to SB-P8B2 or SB-P3G2 was bactericidal, while SB-P1G10 treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 20 publications
1
31
0
Order By: Relevance
“…94 SB-P3G2 and SB-P8B2 were found to have modest activity against non-replicating M. tuberculosis cells grown under low oxygen conditions, which suggested that this series of compounds might have efficacy against latent TB infections. 95 In the in vivo efficacy study of SB-P3G2 and SB-P17G-A20 using an acute TB infection model in GKO mice showed SB-P3G2 reduced the bacterial load of M. tuberculosis H37Rv by 0.7 ± 0.17 log 10 CFU in the lungs and 0.41 ± 0.36 log 10 CFU in spleen, 95 while SB-P17G-A20 reduced the bacterial load by 1.73 ± 0.24 log 10 CFU and 2.68 ± 0.48 log 10 CFU in lungs and spleen, respectively. 94 …”
Section: Ftsz Inhibitorsmentioning
confidence: 99%
“…94 SB-P3G2 and SB-P8B2 were found to have modest activity against non-replicating M. tuberculosis cells grown under low oxygen conditions, which suggested that this series of compounds might have efficacy against latent TB infections. 95 In the in vivo efficacy study of SB-P3G2 and SB-P17G-A20 using an acute TB infection model in GKO mice showed SB-P3G2 reduced the bacterial load of M. tuberculosis H37Rv by 0.7 ± 0.17 log 10 CFU in the lungs and 0.41 ± 0.36 log 10 CFU in spleen, 95 while SB-P17G-A20 reduced the bacterial load by 1.73 ± 0.24 log 10 CFU and 2.68 ± 0.48 log 10 CFU in lungs and spleen, respectively. 94 …”
Section: Ftsz Inhibitorsmentioning
confidence: 99%
“…3), were found to be bactericidal through kill characteristics analysis [31]. It has also be shown that 1 and 2 are active against non-replicating Mtb grown under low oxygen conditions [31], which is unexpected and very exciting since it indicates that these compounds have potential to be effective against latent TB infection.…”
Section: Effects Of the Fluorine And Organofluorine Substitutions mentioning
confidence: 99%
“…To assess the performance of the SMEDDS formulation on the delivery and efficacy of diphenyl ether lead candidates, and co-treatment, SB-PT070 and SB-PT091 were tested in combination with RIF using SMEDDS in our rapid murine Mtb infection model of dissemination described previously 18, 19 In this rapid model to assess drug efficacy, bacteria a delivered to the lungs and treatment is initiated day 5 post infection before the bacteria disseminate to the spleen. Since we have found that dissemination is important to the pathogenesis of tuberculosis as well as other respiratory pathogens, drugs and drug candidates that control dissemination from the infection sight of the lungs to secondary locations such as the spleen are more efficacious at controlling prolonged infection and relapse 33-37 .…”
Section: Resultsmentioning
confidence: 99%
“…18, 19 In this rapid model animals are infected using the low dose aerosol infection followed by treatment for 10 consecutive days starting 5 days post infection. Compounds were solubilized in specified formulations and delivered at the given route and dose.…”
Section: Methodsmentioning
confidence: 99%